The effects of total sleep deprivation on recognition memory processes: A study of event-related potential - Mograss, M.A.; Guillem, F.; Brazzini-Poisson, V.; Godbout, R. (Neurobiology of learning and memory, 2009)
This study examined the memorization of information after a night of normal sleep and total sleep deprivation (TSD) by means of event-related potentials (ERPs). We expected a disfacilitatory effect of TSD on memory processing. Eighteen subjects were tested twice in a counterbalanced fashion. During the study session, subjects were presented with unfamiliar face stimuli and asked to memorize them for a subsequent memory test. At the test session, the subjects were presented with the studied faces intermixed with “new” faces and asked to indicate the previously presented stimuli. The N100 was used as a covariate to control for the differences in level of vigilance between the two sessions. Sleep deprivation decreased subjects’ ability to discriminate new from previously studied stimuli and decreased the peak amplitude of the early component (N200) to the decrement of performance. In addition, following TSD the amplitude of the late frontal component (LFC), which is thought to reflect contextual processing, was decreased in covariance with the N100 vigilance component. The amplitude of the late posterior component (LPC/P600) was also reduced but was unrelated to the vigilance component of the ERP. Based on prior studies, this LPC reduction can be interpreted to indicate a decrease in information retrieved after TSD. In summary, a night of TSD decreased the amplitude of the ERPs associated with complex episodic memory task stimuli, affected the frontal cortex during episodic retrieval, and prevented the elaboration process. Furthermore, there was an inability to discriminate what is and what is not in memory, possibly due to less local processing of details.